ANALISIS PENGARUH KETEPATAN WAKTU PENGIRIMAN DAN KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN - Adianto, Harna (Aksara Public, 2018)
The company strives to always improve service to its customers. To be able to find out customer satisfaction that must be done by a company that is by making improvements to Service Recovery to the accuracy of the delivery schedule and quality improvement of a product. Timeliness of production will affect the delivery of orders that are in accordance with a predetermined schedule so that it can meet customer expectations and they will most likely reorder for the future. The measurement method used by the writer to see customer satisfaction is the hypothesis that the T test method is obtained for timeliness (X1) is 0.12, product quality (X2) is 0.4 and customer satisfaction (Y) is 0.26 while for correlation is for timeliness (X1 ) is 0.43, product quality (X2) is 0.81 and customer satisfaction (Y) is 1 and for coefficient of determination (rÂ²) is 0.82. From the results above stated that between for timeliness (X1), product quality (X2) is very influential and is related to customer satisfaction (Y) so that it will determine whether or not a company runs smoothly.